Implementation Of The Indonesian House Of The Qur'an Forum Program In Increasing Reading - Heri Heri; Syamsu Nahar; Azizah Hanum OK (At-Tarbiyat, 2022)
This study aims to analyze the Maghrib Reciting Forqin Program (Indonesian Qur'an House Forum) in Eradicating Al-Qur'an Illiteracy in Pantai Cermin District. The research was conducted using qualitative methods by describing the program's implementation. The object of this study is an informant. Research informants are also sources of data or research respondents. The results of this study are: holding recital-like activities in every mosque in the sub-district of Pantaimirmiror, the implementation of the maghrib recitation is held after the maghrib prayer. Constraints the indifferent attitude of parents towards their children in motivating reading and writing the Qur'an; Second, the influence of technology (HP) is extreme, and the participation of parents in fostering Illiteracy of the Qur'an is minimal. Teachers of the Koran are not paid enough incentives. The solution to overcome this is for parents to see the results of their children's recitation by checking the contact book given to students. Students are not allowed to bring cell phones. Teachers must improve ways and methods of teaching the Qur'an, such as the Albarqi Method. The local government and local government and parents should pay more attention to the teachers of the Koran to increase welfare of the teachers of the Koran.